(3GdYHGH GdRGNQ hGddHGH GdaGNQs - (3QVj GdOjf CHj GdaVGFd GdMSf Hf eMeO CHh GdMSf, MjOQ GdUGZGfj, J (B650 (3g` s
(3ChdgG (B:s
(3Chd GdehLhO efgG eGOI baRY , bhdg (B: (3GdbaYI TF THjg HGdRfHjd hbGd GdOjfhQi (B: (3CNHQfi CYQGHi ef QHjYI bGd GdbaYGA TLjQI hCPf GdbaYGA GdJi cCfgG CUGHJgG fGQ aJRhJ s
(3BNQgG (B:s
(3ef eGOI RZa CRGOZa Ci CNP cKjkQG hGdJQcjH jOd Ydi SYI haVd BNQ GdeLdO GdQGHY YTQ ef cJGH hddg GdMeO hjJdhg ai GdeLdO GdNGeS YTQ JQcjH (B( (3RaV(B) s
(3GdeNWhW eYLe ai GddZI Cdag dGHf GdYdbei hRjQ GdeSJYUe HgG CKQ WeSs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B214s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdChd (B- (3bSe GdKGfi (B- (3U (B152 s
Keywords: (3GddZIs